Concurrent Force Feedback on Load Symmetry in Total Knee Arthroplasty Patients - Steni Sackiriyas; Becky Heinert; Drew Rutherford; Gwen M Fritz; Thomas W Kernozek (North American Sports Medicine Institute, 2023)
# Background and Purpose Load asymmetry can be present before and after total knee arthroplasty (TKA), which may affect progress during knee rehabilitation in an outpatient sports medicine setting. Current rehabilitation primarily focuses on strength, pain, and range of motion deficits; however, recent evidence suggests the use of movement retraining strategies such as load feedback to address load asymmetry. Therefore, the purpose of this study was to examine how a single session of concurrent force feedback influences load symmetry during the leg-press and body-weight squat exercises in individuals following TKA. Additionally, a secondary purpose was to examine the retention of any changes over the course of a week. # Study design Case-series study # Methods This observational, repeated-measures study design examined the effect of concurrent force feedback training on the mean and standard deviation of load symmetry index during the leg press and squat exercises in 26 patients with TKA in an outpatient sports medicine clinic.The load asymmetry was measured with loadpad sensors placed underneath the each extremity during leg press and squat (baseline), after one training session consisting of concurrent force feedback during these exercises within a single physical therapy session (post feedback), and after seven to ten days of a washout period (post retention). Separate 2 x 3 repeated measures analysis of variance was used to compare the mean and standard deviation of load symmetry across exercise (leg press and squat) and across time (baseline, post feedback and post retention). # Results There was a time effect for the mean load symmetry index (p=0.027) but not for the standard deviation (p=0.441) during these exercises. The leg press showed a greater mean symmetry index compared to the squat regardless of time (p=0.001). # Conclusions A reduction in the mean load symmetry index following concurrent feedback training suggests improved use of the surgical limb during both leg press and squat exercises during the same therapy session but the more symmetric loading pattern was not retained one week later. Overall, the leg press showed greater mean asymmetry than the squat. Standard deviation in the load symmetry index did not change across time or by exercise. # Level of Evidence 3